PERLINDUNGAN HUKUM TERHADAP KREDITUR PADA SEWA MENYEWA TANAH PERTANIAN DENGAN PEMBAYARAN BAGI HASIL DI DESA GIRI EMAS, KECAMATAN SAWAN, KABUPATEN BULELENG - Ni Nyoman Rini Permatasari; Dantes, Komang Febrinayanti; ardhya, si ngurah (Jurnal Ilmu Hukum Sui Generis, 2024)
This research is aimed at finding out and analyzing (1) Legal protection for creditors who experience losses in renting agricultural land with profit sharing payments in Giri Emas Village, Sawan District, Buleleng Regency. (2) Legal consequences for debtors who default on agricultural land rental agreements with profit sharing payments in Giri Emas Village, Sawan District, Buleleng Regency. This research uses research methods. This research uses empirical legal methods which have descriptive research characteristics. The research location was carried out in Giri Emas Village, Sawan District, Buleleng Regency using data collection techniques through document study, observation and interviews. The sampling technique uses a purposive sampling method. The research results obtained were analyzed using qualitative analysis. The results of this research are (1) Protection of Creditors or Land Owners, namely that during the term of the agreement, sharecroppers have the right to work on the land concerned and receive a share of the profits from the land in accordance with the agreement between the two parties. The cultivator is obliged to hand over the land back to the owner and hand over a share of the proceeds from the land managed in good condition at the end of the term of the production sharing agreement. (2) Regarding defaults committed by the Debtor due to overmacht, the Debtor is not obliged to provide compensation even though from the results of research the debtor or cultivator continues to carry out its obligation to pay profit sharing. In accordance with the risk provisions in the rental contract as seen in Article 1553 of the Civil Code, it places both parties to bear the risk in a situation of force (overmacht), without the right of the party who feels aggrieved to ask for compensation.